面向印尼学生的“听说+读写”高效教学模式探析 - Ren Deling (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2024)
In response to the actual needs of Indonesian students in learning Chinese,Sekolah Tinggi Bahasa Harapan Bersama in Pontianak and the College of Chinese Language and Culture of Jinan University have cooperated to open an efficient teaching model of